Avaliação in vitro da efetividade de diferentes pastas antibióticas utilizadas para curativos endodônticos sobre o E. faecalis - Santiago, Adriana Kelly de Sousa (2013)
There is an agreement that in dental treatments with incomplete rizogenese it is necessary an intracanal medication with high antibacterial effect because the use of files and standard protocol based on instrumentation must be avoided to protect the fragile dental element from extra hazard. Several endodontic dressings have been used with this purpose, alone or associated to a copious irrigation procedure. However, it is not yet standardized in the literature a unique medication with protracted and excellent antimicrobial effect, associated to a feasible handling and insertion into the duct. The purpose of this study was to evaluate the in vitro effectiveness of different antimicrobial pastes currently used as intracanal medication against the pathogen Enterococcus faecalis by means of agar disk diffusion method. Accordingly, it was created a polypropylene device to simulate the release characteristics of the main root canal. The efficacy tests were performed over a period of 30 days. The formulations studied were distributed in triplicate just as follows: Triantibiotic Paste (metronidazole, ciprofloxacin and minocycline); Biantibiotic Paste (metronidazole and ciprofloxacin); Ciprofloxacin Paste; Amoxilin Paste; Calcium hydroxide paste; 0.9% saline (control group). All pastes were still allotted into 2 categories: open and closed apex. The devices remained in the medium at 37ºC over 30 days (static). Samples used for the measurement of biologic response were collected in pre-fixed times: H1(1st hour), H6(6th hour), H24(24th hour), D3(3rd day), D7(7th day), D14(14th day) and D30(30th day) in the course of thirty days. At every settled time, 20μL of solution was removed from each device and embedded on sterile paper discs with 6mm of diameter, being the equivalent volume replaced with fresh release medium. After, the discs were transferred with sterile tweezersg to the surface of agar-BHI medium previously inoculated with bacteria over petri plaques. From the devices with closed apex, it was removed 20μL of solution from above the paste surface, avoiding any directly touch on it. This collect aimed to evaluate the antimicrobial effect of different preparations inside the root canal. From the devices with open apex it was removed 20μL of the solution in which the plastic device was submerged, in order to measure the action of the diffused antibiotic to the periapical region through the apex. From the inhibition halos obtained in each case it was possible to rank the formulations in order of effectiveness. The Amoxicillin paste presented an initial antimicrobial effect more robust, keeping it throughout the experiment. However from the second week there was no more significant difference between this and the other antibiotic pastes (triantibiotic and biantibiotic). These pastes had an initial effect less representative than amoxicillin, however the effect became similar from the second week. Nevertheless, calcium hydroxide paste had a discreet effect initially and it was completely ceased already after the 3rd day. Even if Amoxicillin paste presented a superior result among the studied pastes, it was noticed color changes associated to degradation signs after two weeks. The findings show that these antibiotics pastes posed an excellent pharmacological effect, apart from calcium hydroxide. It can be concluded that all the antibiotics pastes, among them the pastes of amoxicillin, triantibiotic and biantibiotic were effective against E. faecalis. As a result its use as dressing for teeth with incomplete risogenesis in may be a good alternative. Among the advantages it is the microbial effectiveness, as well as the feasible manipulation during the clinical procedure. When comparing biantibiotic and triantibiotic pastes, the first showed to be almost equally effective, being a great choice for the clinical treatments of anterior teeth, where the pigmentation caused by minocycline antibiotic could present a drawback in the final result of the treatment.